2009
DOI: 10.1016/j.bcp.2009.03.027
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear budding mechanism in transiently arrested cells generates drug-sensitive and drug-resistant cells

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A c c e p t e d M a n u s c r i p t 1 2 3 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…We showed that HCT116 cells induced to senescence did not enter mitosis but endoreduplicated, what was reflected by increase of DNA content (>16C) an impressive enlargement of nuclei and the lack of typical markers of mitosis [72]. Just recently our results were confirmed by others [88]. On the other hand, others showed that hepatoma cells induced to senescence became polyploidy by endomitosis which led to micronucleation [12].…”
Section: Polyploidization Of Cancer Cells Induced To Senescencesupporting
confidence: 68%
“…We showed that HCT116 cells induced to senescence did not enter mitosis but endoreduplicated, what was reflected by increase of DNA content (>16C) an impressive enlargement of nuclei and the lack of typical markers of mitosis [72]. Just recently our results were confirmed by others [88]. On the other hand, others showed that hepatoma cells induced to senescence became polyploidy by endomitosis which led to micronucleation [12].…”
Section: Polyploidization Of Cancer Cells Induced To Senescencesupporting
confidence: 68%
“…This phenomenon appears to resemble the ''nuclear budding'' fashion of cell division, recently termed neosis, in human cancer cell lines (Rajaraman et al, 2005). The cancer cells first become polyploid upon a drug treatment, and then some of them undergo karyokinesis via nuclear budding followed by asymmetric, intra- (Mansilla et al, 2009;Rajaraman et al, 2005), indicating that a new genetic makeup has been attained in these cells. The spore budding phenomenon most frequently occurring in octaploid tam-2 raises the possibility that neosis may be a common phenomenon in polyploids of both animals and plants.…”
Section: Discussionmentioning
confidence: 87%
“…Intriguingly, a preliminary assessment of p53-null A431 (polyploid) pools with acquired auto-resistance to the CRM metformin has revealed an unexpected phenotype: the generation of haploid cells. We are currently evaluating if parasexual somatic reduction (i.e., nuclear budding or "neosis") [23][24][25] and/or sexual reduction (i.e., meiosis) 26,27 could explain how metformin-induced giant polyploid cells efficiently evade death via mitotic catastrophe. 28,29 Because polyploidization by endocycles of DNA synthesis in the absence of cytokinesis may increase the cell mass and metabolic output and might confer survival value on the cell, these on-going experimental models may reveal how molecular co-evolution of the energy-sensing cytokinetic tumor suppressor AMPK within the AMPK activating biophysical constraints of the tumor microenvironment may provide a "metabolic mode" to generate new progenies of tumor-initiating cells with stem cell-like properties.…”
Section: Ampkmentioning
confidence: 99%